Communication Politics in Sports Events ( Politicization or Political Sports Event ) - Meistra Budiasa (Faculty of Law, Universitas Pekalongan, 2024)
In the modern era, sports become more from simply show Athletics form physique or performance through something event sport ; in its development own role as part from room communication politics. This article explore How communication politics and events sport each other related , as well How government use sport as tool diplomacy and communication. With use analysis qualitative based literature and studies case through event sport big like Olympics and world cup, research This identify How sport has become Medan fight ideology and tools For strengthen image of the country on stage international. A number of sporting events big like The Olympics and World Cup have been used by countries as chance For promote a political agenda they 're nice in a way explicit nor implied. On the other hand, athletes and teams also take advantage event the For convey message politics, sometimes against policy government they Alone. Research result This show that sports, in its capacity as event global communications, has become instrument strategic in communication politics. With Thus, deep understanding about dynamics This important for government and stakeholders interest other in planning communication strategies politics in the current global era This.